2012
DOI: 10.1038/ejcn.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet, breastfeeding and adolescent body composition: a 16-year prospective study

Abstract: BACKGROUND/OBJECTIVES: Overweight and obesity are becoming increasingly prevalent problems worldwide. A number of factors in early life have been found to be associated with body composition of neonates or young children but there is limited follow-up data for adolescents. This study aims to describe associations between early nutrition and body composition in adolescents. SUBJECTS/METHODS: Birth cohort study of 415 pregnant women and their offspring (mean age 16 years). Body composition including fat mass (FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 41 publications
2
47
0
2
Order By: Relevance
“…In our study, all significant associations in the crude models were no longer significant after adjustment for sociodemographic and lifestyle factors. Other studies that did find associations between maternal diet during pregnancy and child body composition did not always adjust for maternal covariates, such as maternal folic acid use (9,13) or prepregnancy BMI (10,13), which were important confounders in our analyses. In addition, the study that reported the association between a high meat intake and a high fat mass in 16-yold adolescents (13) may have the benefits of the longer follow-up period, but this also increases the risk of residual confounding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study, all significant associations in the crude models were no longer significant after adjustment for sociodemographic and lifestyle factors. Other studies that did find associations between maternal diet during pregnancy and child body composition did not always adjust for maternal covariates, such as maternal folic acid use (9,13) or prepregnancy BMI (10,13), which were important confounders in our analyses. In addition, the study that reported the association between a high meat intake and a high fat mass in 16-yold adolescents (13) may have the benefits of the longer follow-up period, but this also increases the risk of residual confounding.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies did not replicate these findings (11,12). Only one study investigated food group intake during pregnancy, which showed that a higher maternal meat intake was associated with a higher fat mass in adolescents, but no associations with vegetables, fish, fruit, and milk were found (13). All of these studies investigated single nutrients or foods, but people do not eat isolated nutrients or foods but whole diets instead.…”
Section: Introductionmentioning
confidence: 85%
“…More specifically, breast milk contains complex immune factors as well as nutrients that are essential for immune system development (Iyengar & Walker, 2012). Breastfeeding has been linked to increased protection against the development of childhood type 1 diabetes mellitus (Rosenbauer, Herzig, & Giani, 2008), asthma (Scholtens et al, 2009), and obesity (Yin, Quinn, Dwyer, Posonby, & Jones, 2012). Emphasizing these significant benefits of breastfeeding compared to BMS may help to promote breastfeeding among educated and urban women and increase the prevalence of breastfeeding in China.…”
Section: Resultsmentioning
confidence: 99%
“…[118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] Overall, although poor quality diets seem to have detrimental effects in the offspring, they are unlikely to be mediators of changes associated with maternal obesity but probably represent an independent risk factor. Studies have also evaluated the association between type of dietary fat and child health outcomes.…”
Section: Dietary Patterns and Nutrient Changesmentioning
confidence: 99%